Optimization of structure and preparing conditions of HTSC (Bi0.8Pb0.2)2(Sr1-yBay)2Ca2Cu3O10+ to Obtain the Highest T - Makadsi, M.; Hermiz, G.; AL-Ani, S.; AL-Shakarchi, KH. (Iraqi Journal of Science, 2025)
High temperature superconductors with a nominal composition (Bi0.8Pb0.2)2(Sr1-yBay)2Ca2Cu3O10+ for y equals to (0,0.1,0.2,0.3,0.4) were prepared by a solid state reaction method .The effect of sintering time ,sintering temperature, oxygen content and barium addition on the superconductivity has been investigated to obtain the optimum conditions for the formation of the high Tc ph(2223). It has been found that a small amount of (Ba=0.1) raises the transition temperature from 80 to 122K while when Ba equal 0.3 there is a decrease of Tc to 98K, and for Ba equals 0.4 itsemiconductor. X-ray diffraction showed an orthorhombic structure with an increase of cell volume and the peaks of the high-Tcthat has no barium content. Scanning electron microscopy has been used to evidence the morphology of the superconducting phases .